Heme acts through the Bach1b/Nrf2a-MafK pathway to regulate exocrine peptidase precursor genes in porphyric zebrafish - Shuqing Zhang; Minrui Xu; Jian Huang; Lili Tang; Yanqing Zhang; Jingyao Wu; Shuo Lin; Han Wang (The Company of Biologists, 2014)
Using a zebrafish model of hepatoerythropoietic porphyria (HEP), we identify a previously unknown mechanism underlying heme-mediated regulation of exocrine zymogens. Zebrafish bach1b, nrf2a and mafK are all expressed in the zebrafish exocrine pancreas. Overexpression of bach1b or knockdown of nrf2a result in the downregulation of the expression of the exocrine zymogens, whereas overexpression of nrf2a or knockdown of bach1b cause their upregulation. In vitro luciferase assays demonstrate that heme activates the zymogens in a dosage-dependent manner and that the zymogen promoter activities require the integral Maf recognition element (MARE) motif. The Bach1b-MafK heterodimer represses the zymogen promoters, whereas the Nrf2a-MafK heterodimer activates them. Furthermore, chromatin immunoprecipitation (ChIP) assays show that MafK binds to the MARE sites in the 5' regulatory regions of the zymogens. Taken together, these data indicate that heme stimulates the exchange of Bach1b for Nrf2a at MafK-occupied MARE sites and that, particularly in heme-deficient porphyria, the repressive Bach1b-MafK heterodimer dominates, which can be exchanged for the activating Nrf2a-MafK heterodimer upon treatment with hemin. These results provide novel insights into the regulation of exocrine function, as well as the pathogenesis of porphyria, and should be useful for designing new therapies for both types of disease.